Impact of COVID-19 Pandemic on Pediatric Infectious Disease Telehealth Practices in North America. Issue 1 (1st November 2022) - Kalyoussef, Sabah; Hakim, Amin; Kumar, Ambuj; Fanella, Sergio; Mohandas, Sindhu; Gaviria-Agudelo, Claudia; ,
Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic has driven a significant increase in the use of telehealth (TH) but little is published about changes in TH usage by pediatric infectious disease (PID) providers. We assessed their pre- and intra-pandemic TH usage and experience. Methods: The Pediatric Infectious Diseases Society Telehealth Work Group surveyed PID specialists in the United States and Canada from 6 December 2020 until 26 February 2021. Data collected included TH modalities, barriers, and satisfaction. Results: The survey response rate was 11.3% (288 of 2, 550 PID clinicians) with 243 (96% of 253 analysis-eligible responses) managing children only. Women accounted for 62.1% ( n  = 157), 51.4% (130) of respondents devoted 50–99% of their time to direct patient care, and 93.3% (236) were located in the United States. The greatest increase in TH usage during the pandemic was in synchronous provider–patient communications (3.9-fold increase). During the pandemic, provider–provider TH increased by less than 10%, comfort with TH usage doubled from 42% to 91%, and satisfaction grew from 74% to 93.3% with different aspects of TH. The top challenge was incomplete or no physical examination (182, 71.9%). Multivariate analysis showed that pre-pandemic TH usage and lack of barriers, but not reimbursement, were significantly associated with higher intra-pandemic usage. EMR-integrated TH was associated with significantly higher usage and satisfaction. Over 70% of respondents anticipate continuing TH usage after the pandemic. Conclusions: There was high intra-pandemic usage of, and increased comfort and satisfaction with telehealth by PID specialists. Our data help inform post-pandemic TH expectations and strategies.